Effects of Whole Body Electromyostimulation on Physical Fitness and Health in Postmenopausal Women: A Study Protocol for a Randomized Controlled Trial - Pano-Rodriguez, Alvaro; Beltran-Garrido, Jose Vicente; Hernandez-Gonzalez, Vicenç; Reverter-Masia, Joaquim (Frontiers in Public Health, 2020)
Background: Age-related problems such as chronic diseases, functional limitation and dependence, reduce the quality of life in the elderly, and increase public spending in health. It has been established that physical activity plays a fundamental role in the health of the elderly. The whole body electromyostimulation (WB-EMS) could be a successful methodology as high-intensity training to improve the physical fitness of older people. Methods: A minimum of 13 women between 55 and 70 years old will be randomized in two groups. The exercise with WB-EMS group (EX + WB-EMS) will conduct a resistance strength training program with superimposed WB-EMS while the exercise group (EX) will perform only resistance strength and aerobic training. Balance, strength, flexibility, agility, speed, and aerobic performance (EXERNET battery and progressive resistance test), as well as body composition, blood parameters and physical activity reporting (IPAQ-E) will be assessed to analyze the effects of whole body electromyostimulation in the physical fitness and the health in postmenopausal women. Discussion: Innovative and scientifically well-designed protocols are needed to enhance the knowledge of the body's responses within this training methodology which is being used by a big quantity of population. This trial will provide evidence on the effectiveness of whole-body electromyostimulation in physical fitness and health in elderly women. Trial Registration: ISRCTN15558857 registration data: 27/11/2019 (retrospectively registered).